Regional differences for the impacts of ecosystem services on farmers’ wellbeing: a case study of the Loess Plateau, China - Chen, Wenting; Liu, Di; Zhang, Jie (Frontiers in Environmental Science, 2024)
Introduction: Different land use patterns affect access to ecosystem services as well as differences in farmers’ well-being. Methods: The Loess Plateau, which has a fragile ecological environment, was chosen as the study region. On the one hand, information on the importance and accessibility of ESs, as well as the subjective and objective well-being of farmers, was obtained through semistructured interviews and questionnaires. On the other hand, regional differences for the impact of ESs on the well-being of farmers were explored based on a structural equation model. Results: The results indicated that the impact of ESs on farmers’ well-being was crucial for all three village types, but the extent of the impact varied, and the key ESs varied across villages. For hilly villages and gully villages, crops and firewood were the two common ES types that were important. However, water conservation was the key ES type for farmers in hilly villages, and pest control was the key ES type for farmers in gully villages. Fruits, water conservation and recreation were the key ES types in the river villages. Discussion: A focus on the regional differences for the impacts of ESs on farmers’ well-being is meaningful for policy practice. We can contribute to farmers’ well-being by optimising land use allocation and land ecological control to improve their ES access in different regions, which is effective in differentiating and enhancing the sustainability of different regions.